Potensi CSR Official Website MNC Peduli Dalam Membangun Citra Perusahaan - Tjantika, Nabilah; Triartanto, A. Yuda; Armelsa, Dhefine (Brand Communication, 2023)
The existence of CSR in today's digital era requires effective and efficient communication in building the company's image. Roles and responsibilities also continue to increase. Increasing pressure and validation mean that humans are required to try more. The aim of this research is to determine the CSR potential of the MNC Peduli Official Website in building the company's image. This research uses qualitative research methods using a descriptive approach. The unit of analysis in this research is the CSR Official Website of MNC Peduli at the MNC Group company. Data collection techniques using interviews and documentation. The results of this research show that MNC companies, in building their corporate image, approach the community by creating activity programs in the social sector which are then published via the official MNC Peduli website.